The Association of Antiretroviral Therapy and Hypertension among HIV-positive Individuals in Canada and Tanzania - So, Geoffrey (My University, 2011)
Introduction: Hypertension is an important worldwide public health concern and is a concomitant risk factor for brain, kidney and cardiovascular disease, such as myocardial infarction (MI). Highly Active Antiretroviral Therapy (HAART) has greatly increased life expectancy of HIV-positive persons, but has been associated with adverse effects.
Objectives: To assess the association between antiretroviral therapy and incident hypertension; to estimate the incidence of hypertension; and to explore known and potential risk factors for hypertension among HIV-positive individuals in Tanzania and Canada.
Methods: Subjects, 18 years and older, were enrolled into two retrospective cohort studies in Tanzania and Canada. Population and descriptive characteristics were summarized. Hypertension was defined as having a SBP>140 mmHg, DBP>90 mmHg, a diagnosis of high blood pressure, or receiving antihypertensive therapy. Statistical analyses, including independent t-tests, Chi-square tests, multiple linear regression, multivariable logistic and Cox regression were performed to assess for statistical significance (p<0.05) in SPSS14.0.
Results: In Tanzania, 52 HIV-positive, normotensive subjects initiating antiretroviral therapy were enrolled. Subjects had a mean age (SD) of 39.5 (7.9) years, were predominantly Black and 53.8% were male. After one year, 4 (7.7%, 95% CI: 2.1-18.7%) developed hypertension. Blood pressure, weight and body mass index (BMI) significantly increased (p<0.05) by 12 months.
In Canada, 486 HIV-positive and normotensive subjects were enrolled; 303 (62.3%) initiated antiretroviral therapy and 183 (37.7%) remained ARV-naive during the study. Subjects were predominantly White (>70%) and male (>75%) with a mean age (SD) of 45.1 (10.0) years. Nine-year incidence of hypertension for ARV-treated and ARV-naïve cohorts was 12.5% (95% CI: 8.8-16.2%) and 8.2% (95% CI: 4.2-12.2%) respectively. Hypertensive individuals were significantly older, heavier, and more likely to have abnormal lipids.
In the final multivariable Cox regression model for incident hypertension, antiretroviral therapy was associated with a 125% increased risk (p=0.018), adjusted for age, sex and race. Individuals >50 compared to <40 years had an increased risk of approximately>280% (p=0.003). Current weight (10 kg increments) was associated with a 37% increased risk (p<0.001). An inverse association between CD4-T-lymphocyte count change and hypertension was observed: a positive change of >500 cell/ml compared to a decrease in CD4-T-lymphocyte count was associated with an 80% lower risk (p=0.032).
Conclusion: Hypertension is common among HIV-positive individuals in Tanzania and Canada and expected to increase over time. Hypertension is associated with antiretroviral therapy; however, further research is needed to understand this relationship.
Keywords: Clinical Epidemiology; Clinical Epidemiology